The History Of Republic Indonesia: Defend And Reinforce To Be Up Againts Insurgiencies - Nurbaity, Nurbaity; Tundjung, Tundjung (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
The important thing from ‘Boedi Oetama” is in his body seeds the spirit of nationalism that had emerged, so that they could be seen as the starting point of the national movement. The youth group then founded the Jong Java association, Jong Sumatran Bond, Jong Minahasa, Jong Ambon, Jong Celebes. Subsequently a new association called Jong Indonesia was formed, aimed at realizing the ideals of Indonesian unity on the basis of nationalism. Starting from the spirit of nationalism, the young people continued to struggle to break away from the colonialism of the Dutch East Indies and Japanese governments. The main objective is to realize the unitary state of the Republic of Indonesia. The struggle was finally successful with the statement of independence read by Sukarno-Hatta on August 17, 1945. After the formation of the unitary state of the Republic of Indonesia did not mean that the struggle of the nationalists was over. The unitary state of the Republic of Indonesia must repeatedly face internal undermining carried out by several groups. Starting from the rebellion of the left in 1948; in the 1950s there was an APRA rebellion, an Andi Azis rebellion, an RMS rebellion, a DI / TII rebellion; and the PKI revolt in 1965. The problem that then arises is how can the Republic of Indonesia overcome various rebellions? In this paper we will review the characteristics of rebellion, is there a common thread between one rebellion and another rebellion? Besides that, it will also be discussed whether there are general patterns used to overcome rebellion. The ability to overcome various parties that undermine, would increasingly strengthen the Republic of Indonesia as a sovereign country. Key words: Republic of Indonesia , the rebellion, nationalism